Avaliação do índice de sobrecarga em cuidadores de crianças com microcefalia no estado da Paraíba - Pereira Júnior, Newton da Silva (2020)
Congenital anomalies can be defined as functional and structural changes in the body resulting in the process of morphogenesis at the birth. Among these anomalies is microcephaly, which is a malformation in which the brain does not develop properly, which can cause functional changes that require special care. Often the care action generates a burden for the caregiver, leading to a perception beyond the must attributed to him, compromising his own health due the cared for some person. The aim of this study was to develop a decision model for the burden index in caregivers of children diagnosed with microcephaly in the state of Paraíba. This is an analytical and longitudinal study, with a quantitative and qualitative approach, using primary data, aiming to analyze the burden of caregivers of children diagnosed with microcephaly in the state of Paraíba, between the periods of 2017 and 2018. The majority of caregivers (43,4%) had severe burden. Only 28,3% say they feel extremely overwhelmed. However, when analyzing the caregivers' discourse, it is noted that daily care makes these women feel more overwhelmed than they seem and without time to take care of themselves, suggesting a high degree for this condition. Thus, it was possible to elaborate a decision support model to assess the level of burden in caregivers of children with microcephaly in the state of Paraíba. This decision model can be applied in order to find reference data for future follow-up studies to understand and cope with burden on caregivers of children with other diagnoses involving multiple disabilities.